Voluntaristict Action In Interaction Between Guest-Student and Local Community In Kampung Inggris - Maghfiroh, Mauliana; Elizabeth, Misbah Zulfa; Sofian, Akhriyadi (Universitas Negeri Semarang, 2023)
The development of Kampung Inggris in Tulungrejo Village, Pare, Kediri has attracted the wider community's attention. Social interaction between local communities and guest-students (language course participants) is an inevitable social process. Parsons's view of voluntaristic action illustrates that the actions taken by a person are based on the impulse of will, by heeding agreed values, ideas and norms. The qualitative mrthods are used to reveal in detail the voluntaristic action by local communities and guest-students. The results of this study indicate that interactions that exist between guest-students and the local community in Kampung Inggris Tulungrejo Village are relationships that influence each other, in which both parties get the benefit from this interaction whether they have the same purpose or not. The interaction between guest-students and the local community is the cooperation that is also established between the owners of the language course institutions with the government and local community of Kampung Inggris, Tulungrejo Village.